Answer:
Step-by-step explanation:
1 ) Given that
[tex](d^2y/dx^2) + 4y = x - x^2 + 20\\\\ (d^2y/dx^2) + 4y = - x^2 + x + 20[/tex]
For a non homogeneous part [tex]- x^2 + x + 20[/tex] , we assume the particular solution is
[tex]y_p(x) = Ax^2 + Bx + C[/tex]
2 ) Given that
[tex]d^2y/dx^2 + 6dy/dx + 8y = e^{2x}[/tex]
For a non homogeneous part [tex]e^{2x}[/tex] , we assume the particular solution is
[tex]y_p(x) = Ae^{2x}[/tex]
3 ) Given that
y′′ + 4y′ + 20y = −3sin(2x)
For a non homogeneous part −3sin(2x) , we assume the particular solution is
[tex]y_p(x) = Acos(2x)+Bsin(2x)[/tex]
4 ) Given that
y′′ − 2y′ − 15y = 3xcos(2x)
For a non homogeneous part 3xcos(2x) , we assume the particular solution is
[tex]y_p(x) = (Ax+B)cos2x+(Cx+D)sin2x[/tex]